Interval observer based control via event-triggered scheme: from single harmonic oscillator to the coupled ones. (11th March 2023) - Wang, Xiaoling; Ming, Tianhang; Lou, Yang; Wang, Lin
This paper deals with the control for single harmonic oscillator system and the coordination control for coupled harmonic oscillators system with unknown additive disturbance and unknown initial states, which are together named the uncertainties, by using the event triggered information. With the boundary information of the uncertainties, an event-triggered interval observer is firstly constructed for the single harmonic oscillator system to realise the interval estimation of state and the robust control of the system. Then, another event-triggered distributed interval observer is constructed to accomplish the interval estimation on the state of each harmonic oscillator and the robust coordinated control of the coupled harmonic oscillator systems. Zeno behaviour can be ruled out for both the single harmonic oscillator and the coupled one. All the theoretical results are verified by numerical simulations.